PENGARUH MODEL PEMBELAJARAN TAKE AND GIVE TERHADAP MINAT BELAJAR PJOK DI KELAS IV SD NEGERI 060933 MEDAN - Anastasia Desmeria Br Ginting; Winara; Apiek Gandamana; Nurmayani; Fajar Sidik Siregar (STKIP Subang, 2026)
This study aims to examine the effect of implementing the Take and Give learning model on students’ interest in Physical Education (PJOK) in Grade IV at SD Negeri 060933 Medan. The research used a Pre-Experimental Design with a One Group Pretest–Posttest design. The population in this study consisted of all fourth-grade students at SD Negeri 060933 Medan, with a sample of 24 students. The independent variable in this study was the Take and Give learning model, while the dependent variable was students’ learning interest. The research instruments used were a Likert-scale questionnaire on learning interest and an observation sheet. Data collection was carried out through initial, during, and final learning observations, as well as pre-test and post-test questionnaires. The data were analyzed using normality tests, homogeneity tests, and hypothesis testing with a paired sample t-test. The results showed an increase in the average students’ learning interest from 2.13 in the pre-test to 3.29 in the post-test. Based on the t-test results, the calculated t-value was -10.254 with df = 23 and a significance value (Sig.) of 0.001 at a 0.05 significance level; therefore, H₀ was rejected and Hₐ was accepted. Thus, it can be concluded that the Take and Give learning model has a significant effect on the learning interest of Grade IV students at SD Negeri 060933 Medan in PJOK, particularly in the material of locomotor movement combinations.